Low thyroxine serves as an upstream regulator of ecophysiological adaptations in Ansell’s mole-rats - Gerhardt, Patricia; Begall, Sabine; Frädrich, Caroline; Renko, Kostja; Heinrich, Alexandra; Köhrle, Josef; Henning, Yoshiyuki (Frontiers in Endocrinology, 2024)
About 10% of all rodent species have evolved a subterranean way of life, although life in subterranean burrows is associated with harsh environmental conditions that would be lethal to most animals living above ground. Two key adaptations for survival in subterranean habitats are low resting metabolic rate (RMR) and core body temperature (Tb). However, the upstream regulation of these traits was unknown thus far. Previously, we have reported exceptionally low concentrations of the thyroid hormone (TH) thyroxine (T4), and peculiarities in TH regulating mechanisms in two African mole-rat species, the naked mole-rat and the Ansell's mole-rat. In the present study, we treated Ansell's mole-rats with T4 for four weeks and analyzed treatment effects on the tissue and whole organism level with focus on metabolism and thermoregulation. We found RMR to be upregulated by T4 treatment but not to the extent that was expected based on serum T4 concentrations. Our data point towards an extraordinary capability of Ansell's mole-rats to effectively downregulate TH signaling at tissue level despite very high serum TH concentrations, which most likely explains the observed effects on RMR. On the other hand, body weight was decreased in T4-treated animals and Tb was upregulated by T4 treatment. Moreover, we found indications of the hypothalamus-pituitary-adrenal axis potentially influencing the treatment effects. Taken together, we provide the first experimental evidence that the low serum T4 concentrations of Ansell's mole-rats serve as an upstream regulator of low RMR and Tb. Thus, our study contributes to a better understanding of the ecophysiological evolution of the subterranean lifestyle in African mole-rats.